Let's analyze each system of equations individually.
System A:
- \( 5x - y = -9 \)
- \( -5x + y = 9 \)
To solve this system, we can rearrange the second equation:
From the second equation: \[ -5x + y = 9 \implies y = 5x + 9 \]
Now substitute \( y \) into the first equation:
\[ 5x - (5x + 9) = -9 \] \[ 5x - 5x - 9 = -9 \] \[ -9 = -9 \]
This is a true statement, which indicates that the two equations are dependent (they are essentially the same line represented in different forms). Thus, the system has infinitely many solutions.
Solution for System A:
The solution can be expressed in terms of \( x \): \[ y = 5x + 9 \] Where \( x \) can be any real number.
Summary for System A:
- The system has infinitely many solutions.
System B:
- \( 5x - 6y = 1 \)
- \( -5x + 6y = 2 \)
To solve this system, we can rearrange the second equation:
From the second equation: \[ -5x + 6y = 2 \implies 6y = 5x + 2 \implies y = \frac{5}{6}x + \frac{1}{3} \]
Now substitute \( y \) into the first equation:
\[ 5x - 6\left(\frac{5}{6}x + \frac{1}{3}\right) = 1 \] \[ 5x - 5x - 2 = 1 \] \[ -2 = 1 \]
This is a false statement, indicating that the two equations represent parallel lines that do not intersect. Thus, the system has no solution.
Summary for System B:
- The system has no solution.
Final Answer:
- System A: The system has infinitely many solutions.
- System B: The system has no solution.